Thalidomide Controls Adipose Tissue Inflammation Associated with High- Fat Diet-Induced Obesity in Mice - Z Nakamitsu, Patricia; M. Compri, Cecilia; de Fraia Pinto, Livia; M.F. Gotardo, Erica; C. de Oliveira, Caroline; L. Ribeiro, Marcelo; Pedrazzoli, Jose; Gambero, Alessandra (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2015)
Introduction: Immunosuppressant agents modulate the activity of the immune system and control adipose tissue inflammatory responses associated with obesity. Controlling adipose tissue inflammation represents an interesting option for inhibiting the low-grade inflammatory state in obese subjects and for preventing obesity-associated pathologies. In this work, we assessed the effects of thalidomide on the inflammatory response in adipose tissue as well as on systemic inflammatory marker expression in the well-established high-fat diet-induced obesity mouse model. Methods: Swiss male mice were fed a high-fat diet (60% kcal from fat) for 12 weeks and received thalidomide for the last 10 days (100 mg.kg-1). Adipokine levels were measured in serum and adipose tissue by EIA and real-time quantitative PCR, respectively. Adipose tissue infiltrating macrophages were identified by immunohistochemistry and western blot analysis of F4/80 marker expression. Other inflammatory markers, such as c-Jun N-terminal kinase (JNK) phosphorylation and monocyte chemoattractant protein-1 (MCP-1) production, were also evaluated by western blot analysis. In vitro assays using 3T3-L1 adipocytes were also conducted to evaluated adipokine release. Results: In obese mice, thalidomide administration induced a reduction in adiposity accompanied by a reduction of tumor necrosis factor-α (TNF-α), leptin and MCP-1 adipose tissue production, macrophage infiltration and JNK activation. TNF-α and leptin serum levels were also reduced by thalidomide treatment in obese mice. In vitro, the release of basal TNF-α and lipopolysaccharide (LPS)-induced MCP-1 was inhibited in 3T3-L1 cells. Significance: Our results suggest that drugs that can modulate the inflammatory status as well as control adipose tissue expansion could represent an interesting approach in the management of obesity, highlighting the need for further development of such compounds.
Keywords: macrophage